Plants on islands : diversity and dynamics on a continental archipelago - Cody, Martin L., 1941- (University of California Press, 2006)
This study examines and critically analyses the island biogeography of plants on continental islands in Barkley Sound and is the result of a quarter-century of research. It discusses isolation and climatic differences and the interplay of coexistence and competition on over 200 islands.